Brand-Customer Relationships: Web 2.0 and Online Brand Communities - Guitton, Olivier (2007)
This study aims to explore the characteristics of online brand communities in a Web 2.0 context and to understand in which positive ways they can contributes to the brand and its customers. This staged evolution of the Internet, reinforces interactivity and gives users the possibility to generate their own contents themselves.